1997
DOI: 10.1007/bf02445322
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between factors of nonspecific resistance in shock caused by mechanical trauma or burn

Abstract: Rats with shock caused by mechanical injury or burn showed stereotypic and phasic variations of the absorptive capacity of hepatic reticuloendothelial system, plasma fibronectin content, and functional activity of peripheral blood neutrophils. The direction of alterations in these factors of nonspecific resistance pointed to a depression of the phagocytic system and correlated with the severity of the postinsult states.Key Words: shock; macrophages; neutrophils; fibronectin; phagocytosisThe phagocytic system p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…It has been shown that macro-and microphage suppression against the background of hypofibronectinemia reflects the severity of postaggressive states and usually disappears in natural relieve of the shock [4][5][6]. These findings agree with the published data that organism's resistance to extreme factors strongly depends on the functional state of the phagocytosis system and plasma opsonizing activity [2,9,10,12,15].…”
supporting
confidence: 91%
“…It has been shown that macro-and microphage suppression against the background of hypofibronectinemia reflects the severity of postaggressive states and usually disappears in natural relieve of the shock [4][5][6]. These findings agree with the published data that organism's resistance to extreme factors strongly depends on the functional state of the phagocytosis system and plasma opsonizing activity [2,9,10,12,15].…”
supporting
confidence: 91%